Nodding syndrome, a case-control study in Mahenge, Tanzania: Onchocerca volvulus and not Mansonella perstans as a risk factor. - Luís-Jorge Amaral; Dan Bhwana; Athanas D Mhina; Bruno P Mmbando; Robert Colebunders (Public Library of Science (PLoS), 2023)
Background Nodding syndrome (NS) has been consistently associated with onchocerciasis. Nevertheless, a positive association between NS and a Mansonella perstans infection was found in South Sudan. We aimed to determine whether the latter parasite could be a risk factor for NS in Mahenge. Methods Cases of epilepsy were identified in villages affected by NS in Mahenge, Tanzania, and matched with controls without epilepsy of the same sex, age and village. We examined blood films of cases and controls to identify M. perstans infections. The participants were also asked for sociodemographic and epilepsy information, examined for palpable onchocercal nodules and onchocerciasis-related skin lesions and tested for anti-Onchocerca volvulus antibodies (Ov16 IgG4) by ELISA. Clinical characteristics of cases and controls, O. volvulus exposure status and relevant sociodemographic variables were assessed by a conditional logistic regression model for NS and epilepsy status matched for age, sex and village. Results A total of 113 epilepsy cases and 132 controls were enrolled, of which, respectively, 56 (49.6%) and 64 (48.5%) were men. The median age in cases and controls was 28.0 (IQR: 22.0-35.0) and 27.0 (IQR: 21.0-33.3) years. Of the persons with epilepsy, 43 (38.1%) met the probable NS criteria and 106 (93.8%) had onchocerciasis-associated epilepsy (OAE). M. perstans infection was absent in all participants, while Ov16 seroprevalence was positively associated with probable NS (odds ratio (OR): 5.05, 95%CI: 1.79-14.27) and overall epilepsy (OR: 2.03, 95%CI: 1-07-3.86). Moreover, onchocerciasis-related skin manifestations were only found in the cases (n = 7, p = 0.0040), including persons with probable NS (n = 4, p = 0.0033). Residing longer in the village and having a family history of seizures were positively correlated with Ov16 status and made persons at higher odds for epilepsy, including probable NS. Conclusion In contrast to O. volvulus, M. perstans is most likely not endemic to Mahenge and, therefore, cannot be a co-factor for NS in the area. Hence, this filaria is unlikely to be the primary and sole causal factor in the development of NS. The main risk factor for NS remains onchocerciasis.